A Clinical Study on PCOS Patients in a Tertiary Hospital - Anwary, Shaheen Ara; Alfazzaman, Md; Begum, Nurjahan (Medicine Today, 2010)
Polycystic ovary syndrome (PCOS) is a common condition characterized by menstrual abnormalities and clinical or biochemical features of hyperandrogenism and may manifest at any age. The present study was carried out at Bangabandhu Sheikh Mujib Medical University, Dhaka, from January 2008 to March 2009, on 50 women with PCOS which was diagnosed by three criteria: (1) oligo and/or anovulation, (2) hyperandrogenism and (3) polycystic ovaries, to evaluate their characteristics and laboratory investigation findings. Most common age was 2125 years (44%), mean BMI 27.10 kg/m2, menstrual cycle irregularity 80%, oligomenorrhoea 28%, dysmenorrhoea 18%, nulliparity 90%, history of abortion 10%, acne in 52%, hirsutism in 50%, and per vaginal findings were anteverted uterus 100%, free fornices 98% and healthy cervix 94%. Laboratory findings were low (2.8 mIU/ml) serum FSH 2%, raised (>14.7 mIU/ml) serum LH 56%, raised (7.8 mmol/L) blood sugar (2hr after 75 g glucose load) 30%, raised (>25 ng/ml) serum prolactin 14%, raised (>4 ?IU/ml) serum TSH 2%, low <3.5 ng/dl), ultrasound of lower abdomen showed evidence of PCOS in 100% cases. Infertility in women with PCOS can be treated successfully in most women by diet and exercise, clomiphene citrate with or without metformin, laparoscopic ovarian diarthermy, or ovulation induction with gonadotrophins. Key words: PCOS; Infertility DOI: 10.3329/medtoday.v22i1.5604 Medicine Today Vol.22(1) 2010. 34-37